Selective Involvement of a Subset of Spinal Dorsal Horn Neurons Operated by a Prodynorphin Promoter in Aβ Fiber-Mediated Neuropathic Allodynia-Like Behavioral Responses in Rats - Ishibashi, Tadayuki; Yoshikawa, Yu; Sueto, Daichi; Tashima, Ryoichi; Tozaki-Saitoh, Hidetoshi; Koga, Keisuke; Yamaura, Ken; Tsuda, Makoto (Frontiers in Molecular Neuroscience, 2022)
Mechanical allodynia (pain produced by innocuous stimuli such as touch) is a main symptom of neuropathic pain. Its underlying mechanism remains to be elucidated, but peripheral nerve injury (PNI)-induced malfunction of neuronal circuits in the central nervous system, including the spinal dorsal horn (SDH), is thought to be involved in touch-pain conversion. Here, we found that intra-SDH injection of adeno-associated viral vectors including a prodynorphin promoter (AAV-PdynP) captured a subset of neurons that were mainly located in the superficial laminae, including lamina I, and exhibited mostly inhibitory characteristics. Using transgenic rats that enable optogenetic stimulation of touch-sensing Aβ fibers, we found that the light-evoked paw withdrawal behavior and aversive responses after PNI were attenuated by selective ablation of AAV-PdynP-captured SDH neurons. Notably, the ablation had no effect on withdrawal behavior from von Frey filaments. Furthermore, Aβ fiber stimulation did not excite AAV-PdynP+ SDH neurons under normal conditions, but after PNI, this induced excitation, possibly due to enhanced Aβ fiber-evoked excitatory synaptic inputs and elevated resting membrane potentials of these neurons. Moreover, chemogenetic silencing of AAV-PdynP+ neurons of PNI rats attenuated the Aβ fiber-evoked paw withdrawal behavior and c-FOS expression in superficial SDH neurons. Our findings suggest that PNI renders AAV-PdynP-captured neurons excitable to Aβ fiber stimulation, which selectively contributes to conversion of Aβ fiber-mediated touch signal to nociceptive. Thus, reducing the excitability of AAV-PdynP-captured neurons may be a new option for the treatment of neuropathic allodynia.